Scottish practitioners are used to embracing change - Hazel Whitters (Scottish Journal of Residential Child Care)
I quickly downloaded this month’s publication by CELCIS as I was keen to read the views of the two contributors to the named person debate. Recent months have seen sporadic and intensive coverage from the media on behalf of Government, parents, professionals and interested public. The articles in CELCIS were presented as two sides of a discussion on this significant topic, however, as a reader I identified a great deal of common ground between the authors. I detected a shared passion, the same goals, and a sense of anxiety from Mike Burns and Maggie Mellon.